TechTip: Web-to-email, web pages via email - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
For many people in ACP countries, particularly those living in remote rural areas, non-existent or poor and expensive Internet connections are a daily reality.